Use of Adobe Flash CS 6 Media in Learning Design Skills Competence Modeling and Building Information - Rudiansyah, Akhid Aditia; Hadromi, Hadromi; Yudiono, Heri (Universitas Negeri Semarang, 2021)
This research was carried out based on the results of observations in the vocational theory learning process, there were several obstacles faced, There are several obstacles, namely, 1) the methods used are lectures and discussions that are less than optimal; 2) students are less enthusiastic in learning the material because the media used by the teacher is in the form of power points and softfile modules; 3) It is not possible to use power point media and module softfiles to operate randomly and freely in adjusting the selection of the material pages you want to learn. The research objectives of this research are (1) develop Adobe Flash CS6-based learning media in Vocational Theory subjects,(2) analyze the feasibility and practicality of learning media,(3) analyze the effectiveness of using learning media. Research on the development of learning media based on Adobe Flash CS 6 using the ADDIE development model. The data collection tool for the feasibility of learning media uses media experts. Media practicality data using assessment questionnaires by teachers and students. In the results of this study, Adobe Flash CS 6 can be integrated with server side scripting such as CGI, ASP and PHP to create beautiful database web applications. In addition, it can also be used to make short films or cartoons, presentations, advertisements or web banners, logo animations.